Betta Fish Monitoring System: Development of Water Quality Control and Video Monitoring System - Fakhrul Arifin, Muhammad Umairul Asyraf; Masnani Binti Mohamed; Ahmad, Ida Laila (Evolution in Electrical and Electronic Engineering, 2023)
A betta fish monitoring system with water quality control and a video monitoring system is developed to assist the breeder in cleaning the fish tank and controlling the water quality to ensure the water is clean. It is because breeding and monitoring this betta fish involves a lot of labour and a considerable amount of time to maintain the quality of pure water so that the fish grown are healthy and beautiful. When the betta fish's water condition is dirty, this has spurred the notion of developing a more productive method of betta fish breeding with an automatic water exchange system. In addition, a camera-based surveillance system that enables breeders to monitor the state of their betta fish via internet video can assist breeders in ensuring that their betta fish are in good condition. This system states water cleanliness by adjusting the pH, turbidity, and temperature appropriately for this betta fish. Based on this project, have two types of water replacement: automatic water replacement and manual control water replacement. For automatic water replacement, sensor pH and turbidity will detect water quality. When the quality of water decreases, which is the value of turbidity more than 25 and value pH less than 6.5 and more than 8.5, water will change automatically. For manual water replacement, the user will control the water pump via smartphone using the Blynk application to change the water. At the same time, the breeder can monitor their fish from a video live on the Blynk application. As a result, this product gives betta fish breeders advantages through the use of less labour and the acceleration of the water change procedure for betta fish in a single instance.